Las Señoras de la Caridad: pioneras olvidadas de la asistencia social en México, 1863-1910 - Arrom, Silvia Marina (El Colegio de México, A.C., 2007)
The Asociación de Señoras de la Caridad (Association of Ladies of Charity) was one of the largest Mexican women's organizations during the Porfiriato. It mobilized thousands of lay women volunteers throughout the country, helping hundreds of thousands of poor people, as they strengthened their Catholic faith and values. Besides visiting those in need both in their homes and in public hospitals and jails, these women created and managed their own schools, hospitals, nursing homes, and other welfare institutions, thus contributing to Mexican systems of education, health, and social assistance. Without challenging the social standards of their time, the ladies of Charity carried out novel practices for Mexican women, and expanded the traditional limits of the feminine world.